EFEKTIFITAS PENGELOLAAN AIR MINUM UNTUK RUMAH TANGGA - Nurbaiti Nurbaiti (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Water is one of natural resources that has a very important function for human life. Based on research, the coliform bacteria produces etionin substances that can cause cancer and also illness if the amount was excessive in the body. The purpose of this research was to determine the number of bacteria in the water after doing filtration by using a 0.5 micron and 0.1 micron cartridge to the total of coliform bacteria. Data were analyzed by bivariate analysis using t-test. The results showed that there was no difference to the average number of bacteria that were filtered between the first and the second filtrations. This study was an experimental research design using pre and post-only design. The results based on laboratory testing showed that there was reduction in the number of coliform bacteria after filtering using a 0.5 micron and 0.1 micron cartridge. This filtration can be used to reduce the amount of bacteria in the water and if it is added with a complete tool can be used for water treatment.